A first principles study of a van der Waals heterostructure based on MS2 (M = Mo, W) and Janus CrSSe monolayers. Issue 17 (2nd August 2022) - Alam, Q.; Sardar, S.; Din, H. U.; Khan, S. A.; Idrees, M.; Amin, B.; Rehman, F.; Muhammad, Saleh; Laref, A.
Abstract : The strategy of stacking two-dimensional materials for designing van der Waals heterostructures has gained tremendous attention in realizing innovative device applications in optoelectronics and renewable energy sources. Abstract : The strategy of stacking two-dimensional materials for designing van der Waals heterostructures has gained tremendous attention in realizing innovative device applications in optoelectronics and renewable energy sources. Here, we performed the first principles calculations of the geometry, optoelectronic and photocatalytic performance of MS2 –CrSSe (M = Mo, W) vdW heterostructures. The mirror asymmetry in the Janus CrSSe system allows the designing of two models of the MS2 –CrSSe system by replacing S/Se atoms at opposite surfaces in CrSSe. The feasible configurations of both models of the MS2 –CrSSe system are found energetically, dynamically and thermally stable. The studied heterobilayers possess an indirect type-I band alignment, indicating that the recombination of photogenerated electrons and holes in the CrSSe monolayer is hence crucial for photodetectors and laser applications. Remarkably, a red-shift in the optical absorption spectra of MS2 –CrSSe makes them potential candidates for light harvesting applications. More interestingly, all heterobilayers (except W(Mo)S2 –CrSSe of model-I(II)) reveal appropriate band edge positions of the oxidation and reduction potentials of the photocatalysis of water dissociation into H + /H2 and O2 /H2 O at pH = 0. These results shed light on the practical design of the MS2 –CrSSe system for efficient optoelectronic and photocatalytic water splitting applications.